The Efficacy of “Care for Child Development” Intervention on the Improvement of the Development Skills of Orphanage Children - maleki, zahra; Baraheni, Nasrin; Heidarabadi, Seifollah; Azhdarzadeh, Fatemeh; Bahari Gharehgoz, Ali (Iranian Journal of Child Neurology, 2023)
Objectives Development refers to the progressive enhancement of skills and functional capacity, i.e., qualitative changes in the child’s functions. The process of development begins before birth and continues throughout life. The present study aims to evaluate the effectiveness of the “Care for Child Development (CCD)” program on 4-42 months children’s developmental skills in orphanages. Materials & Methods In this study, two orphanages in the capitals of East and West Azerbaijan provinces were selected using the convenience sampling technique, and thirty children were included. Then, they were randomly divided into two intervention and control groups (each group, N=15). Next, after obtaining consent from the head of the orphanages, a group of volunteers from the healthcare center performed the CCD program, considering children’s chronological ages (4 to 42 months), for three sessions a week, with each session lasting two hours and it lasted for three months. At the end of the intervention process, the Bayley Scale of Infant and Toddler Development 3rd version (BSID-III) and the Ages and Stages Questionnaire-II (ASQ) were completed for the two intervention and control groups to compare them in the cognitive, motor, communication, and personal-social domains. Results Comparing the two control and intervention groups using the T-test (difference in mean) indicates that except for the domain of cognitive skills (Bayley: P-value = 0.176), there was statistically a significant difference between the two groups in communication (ASQ: P-value= 0.001; Bayley: P-value = 0.003), motor (ASQ: P-value = 0.000; Bayley: P-value = 0.009), and personal-social (ASQ: P-value <0.000)skills. Conclusion In the present study, it was concluded that it is required to apply interventions, including standard ones such as the CCD program in environments like orphanages, to enhance the developmental skills of those children living in them